2017
DOI: 10.1002/jso.24637
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐end‐to‐end esophagojejunostomy after laparoscopy‐assisted total gastrectomy better reduces stricture and leakage than the conventional end‐to‐side procedure: A retrospective study

Abstract: SETE EJ is more convenient than the conventional ETS procedure and is associated with a shorter reconstruction time and a lower incidence of EJ stricture and leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, when the left side of the cut end of the esophagus (at the top of the cartridge) is cut and punched, a line of staples can be optimally placed, securing the anastomosis. When the anvil and circular stapler are connected, the distal jejunum close to the circular stapler is placed in cranial, not caudal, traction . Duan et al reported that in end‐to‐side esophagojejunostomy, the anastomosis channel and the food channel were not consistent, the diameter of circular stapler was not equal to that of the anastomotic stoma, and the distal folding intestinal wall could potentially be tacked to the anastomotic stoma, leading to stenosis . Our method, which places cranial traction on the distal jejunum during anastomosis of the esophagus and jejunum, prevents the distal intestinal wall from being tacked to the anastomotic stoma and involves no anastomotic tension that may lead to stenosis. A single‐layer of sutures is placed at points of dog‐ear formation and overlap, and these defects are completely closed with Lembert sutures to reinforce the anastomosis .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, when the left side of the cut end of the esophagus (at the top of the cartridge) is cut and punched, a line of staples can be optimally placed, securing the anastomosis. When the anvil and circular stapler are connected, the distal jejunum close to the circular stapler is placed in cranial, not caudal, traction . Duan et al reported that in end‐to‐side esophagojejunostomy, the anastomosis channel and the food channel were not consistent, the diameter of circular stapler was not equal to that of the anastomotic stoma, and the distal folding intestinal wall could potentially be tacked to the anastomotic stoma, leading to stenosis . Our method, which places cranial traction on the distal jejunum during anastomosis of the esophagus and jejunum, prevents the distal intestinal wall from being tacked to the anastomotic stoma and involves no anastomotic tension that may lead to stenosis. A single‐layer of sutures is placed at points of dog‐ear formation and overlap, and these defects are completely closed with Lembert sutures to reinforce the anastomosis .…”
Section: Discussionmentioning
confidence: 93%
“…Duan et al reported that in end-to-side esophagojejunostomy, the anastomosis channel and the food channel were not consistent, the diameter of circular stapler was not equal to that of the anastomotic stoma, and the distal folding intestinal wall could potentially be tacked to the anastomotic stoma, leading to stenosis. 35 Our method, which places cranial traction on the distal jejunum during anastomosis of the esophagus and jejunum, prevents the distal intestinal wall from being tacked to the anastomotic stoma and involves no anastomotic tension that may lead to stenosis. 3.…”
Section: Anastomotic Leakagementioning
confidence: 99%
“…In addition, TLG in intracorporeal anastomosis had the advantages of high safety, less adhesion, rapid recovery, and small scars (29,30). At present, the related literature (9)(10)(11)(12)(13) reports that esophagojejunostomy is mainly performed with circular and linear staplers. In fact, a variety of techniques for esophagojejunostomy have emerged in recent years, but none of them was considered as the standard technique (31).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, relevant literature (9)(10)(11)(12)(13) reports that esophagojejunostomy is mainly performed with circular and linear staplers. The former mainly includes the transorally inserted anvil (OrVil TM ), reverse puncture device (RPD), and purse-string suture method; the latter mainly includes functional end-to-end (FETE), overlap anastomosis, π-shaped esophagojejunostomy and semi-end-to-end anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [115] 2016 CS RPM 58 199.8 ± 57.0 81.6 ± 40. 3 5Wang et al [96] Duan et al [116] Lee et al [117] 2017 LS Overlap 50 144.6 ± 29.9 NA 0…”
Section: Conclusion and Prospectsmentioning
confidence: 99%